Corrosion Inhibition of Mild Steel in HCl by Isolated Compounds of Riccinus Communis (L.) - Rinki Goel; W. A. Siddiqi; Bahar Ahmed; J. Hussan (E-Journal of Chemistry)
We have isolated three pyridine base alkaloids namely ricinine (C1), N-demethylricinine (C2) and 4-methoxy pyridine-3-carboxylic acid (C3) from methanolic extract of Riccinus Communis leaves and investigated corrosion inhibition effect on mild steel in 0.5 HCl solution using the weight loss and electrochemical techniques (Galvanostatic polarization and EIS). Polarization resistances calculated from the EIS measurements are in good agreement with those obtained from alternating current (AC) polarization measurements. The mild steel samples were also analyzed by Scanning Electron Microscopy (SEM). The results show that C1 is an excellent inhibitor for mild steel in acid medium. The inhibition was assumed to occur via adsorption of the inhibitor molecule on the metal surface. In the 298- 308 K temperature range, the C1, C2 and C3 adsorption follows Langmuir isotherm model. The protection efficiency increases with increasing the inhibitor concentration in the range of 250-1000 ppm but slightly decreases with increasing temperature.